Floriana Znanieckiego idea uspołecznienia do altruizmu - Hałas, Elżbieta (Rocznik Pedagogiczny, 2021)
Certain visionary threads of Florian Znaniecki’s thought present in his sociological theory of educa- tion merit our attention. They are associated with the concept of creating a grassroots movement of new sociality, capable of becoming a vehicle of reflexive social and cultural changes. These utopian threads related to the current of new humanism appear in all of Znaniecki’s works. The problem of altruism seems crucial in the light of Znaniecki’s axiology, but has not been properly examined until now. When Znaniecki names the new social tasks of education with the goal of shaping social changes, he considers the problem of social good from the perspective of intergroup relations. He searches for a new meaning of altruism, especially collective altruism, which would be the antithesis of collective egoism, and thus would transcend the limits of solidarity only with one’s own group. The issue of altruism, so important for Znaniecki, has only recently begun to regain its place in sociology. Znaniecki’s thought can be read in a connection with the contemporary anti-utilitarian movement and the newly revived discussion about the possibility of humanism after modernity.